BKK the EZ Way: International Long-Run Growth News and Capital Flows - Colacito, Ric; Croce, Max; Ho, Steven; Howard, Philip (American Economic Review, 2018)
We study the response of international investment flows to shortand long-run growth news. Among developed G7 countries, positive long-run news for domestic productivity induces a net outflow of investments, in contrast to the effects of short-run growth shocks. We document that a standard Backus, Keho, and Kydland (1994) (BKK) model fails to reproduce this novel empirical evidence. We augment this model with Epstein and Zin (1989) preferences (EZ-BKK) and characterize the resulting recursive risk-sharing scheme. The response of international capital flows in the EZ-BKK model is consistent with the data. (JEL F14, F32, F43, G12)